Vitamin C is a source of oxoaldehyde and glycative stress in age‐related cataract and neurodegenerative diseases. Issue 7 (21st June 2020) - Fan, Xingjun; Sell, David R.; Hao, Caili; Liu, Sabrina; Wang, Benlian; Wesson, Daniel W.; Siedlak, Sandra; Zhu, Xiongwei; Kavanagh, Terrance J.; Harrison, Fiona E.; Monnier, Vincent M.
Abstract: Oxoaldehyde stress has recently emerged as a major source of tissue damage in aging and age‐related diseases. The prevailing mechanism involves methylglyoxal production during glycolysis and modification of arginine residues through the formation of methylglyoxal hydroimidazolones (MG‐H1). We now tested the hypothesis that oxidation of vitamin C (ascorbic acid or ASA) contributes to this damage when the homeostatic redox balance is disrupted especially in ASA‐rich tissues such as the eye lens and brain. MG‐H1 measured by liquid chromatography mass spectrometry is several fold increased in the lens and brain from transgenic mice expressing human vitamin C transporter 2 (hSVCT2). Similarly, MG‐H1 levels are increased two‐ to fourfold in hippocampus extracts from individuals with Alzheimer's disease (AD), and significantly higher levels are present in sarkosyl‐insoluble tissue fractions from AD brain proteins than in the soluble fractions. Moreover, immunostaining with antibodies against methylglyoxal hydroimidazolones reveals similar increase in substantia nigra neurons from individuals with Parkinson's disease. Results from an in vitro incubation experiment suggest that accumulated catalytic metal ions in the hippocampus during aging could readily accelerate ASA oxidation and such acceleration was significantly enhanced in AD. Modeling studies and intraventricular injection of 13 C‐labeled ASA revealed that ASA backbone carbons 4–6 are incorporated into MG‐H1 both in vitro and in vivo, likely via a glyceraldehyde precursor. We propose that drugs that prevent oxoaldehyde stress or excessive ASA oxidation may protect against age‐related cataract and neurodegenerative diseases. Abstract : Oxoaldehyde stress in aging and age‐related diseases is widely believed to stem from advanced glycation end products of glucose via methylglyoxal formation during glycolysis. Here, we demonstrate that ascorbic acid oxidation is a source of damage via methylglyoxal hydroimidazolone formation in long‐lived proteins from tissues rich in vitamin C such as the lens and the brain.